EMC3-EIRENE modeling of edge plasma to improve the ICRF coupling with local gas puffing in DEMO. (20th September 2018) - Zhang, Wei; Franke, Thomas; Noterdaeme, Jean-Marie; Van Eester, Dirk
Abstract: We report the first 3D EMC3-EIRENE simulations of scrape-off layer (SOL) plasma in DEMO. EMC3-EIRENE is a 3D edge plasma fluid and neutral particle transport code. Effects of local gas puffing on the SOL density and ion cyclotron range of frequencies (ICRF) power coupling have been studied. A pure deuterium plasma is simulated and the puffing/fueling gas is deuterium gas. The gas puffing cases investigated include divertor, top, midplane and antenna gas puffing. The ICRF antenna is distributed through 360° toroidally, and poloidally located in the outer top of the vessel. The results show that toroidally distributed but poloidally localized antenna gas puffing increases the density in front of the antenna most significantly, while top or midplane gas puffing increases this antenna density to a moderate level. Influences of gas puff rate and particle transport parameters on the SOL density are investigated. The parameter scans indicate that the shift of the fast wave cut-off density position to the antenna depends almost linearly on the total gas puff rate. To achieve a significant antenna density increase, the antenna gas puff rate should be at the level of 1.8 × 10 23 el s −1 (i.e. 1.0 × 10 22 el s −1 per tokamak segment). As the total gas puff rate increases to 4.0 × 10 23 el s −1, the evanescent layer of the fast wave (with = 2 m −1 ) almost vanishes. Moreover, it is found that antenna gas puffing reduces the local power flux to the main chamber wall near the gas valve due to a local decrease of the SOL temperature.